PRAKTIK AKUNTANSI UNTUK ASET BERSEJARAH STUDI FENOMENOLOGI PADA MUSEUM ACEH - safitri, mia rizky; indriani, mirna (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This study is the phenomenon of the accounting treatment applied to heritage assets in Aceh, both in terms of recognition, valuation, and disclosure in the financial statements. The focus of this study is an analysis of the accounting treatment in the Museum of Aceh. This study aimed to: understand the significance of historic assets (heritage assets), describes the methods used to assess the Museum of Aceh, explaining the Museum of Acehs disclosure in the financial statements, and analyze the appropriateness of the accounting standards applicable to the accounting for current the Museum Of Aceh. The results of this study indicate that there is no precise definition of heritage assets. This is evidenced by the exposure to most of the informants who always associate with the historic definition of asset definition Heritage so there is confusion between the two. In addition, the Museum of Aceh is still experiencing difficulties in assessing valuation on heritage assets . However , the practice of accounting in the Museum of Aceh is not considered to be in accordance with the accounting standards set by the government , which is not presented and disclosed in CaLK without value.Keywords: Heritage Assets , Recognition , Assessment , Disclosure.